Defence and space expenditures in the US: An inter-firm analysis - Alok K. Chakrabarti; Hans H. Glismann; Ernst-Jürgen Horn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
The economic impact of defence and space expenditures has been an important policy issue because of the secondary benefits expected to be accruing from it. Although defence and space activities can stimulate the early development of many technologies, the lasting economic impact of these technologies is difficult to measure. To capture the scientific and technological values added of defence and space financed productions, we have depended on the patents and scientific and technical publications as the indicators. The economic performance has been measured by two separate indicators: (a) firm growth in terms of average annual rate of change in the number of employees, and (b) rate of return on sales measured by the company's net profits in relation to sales. From 1970-75 and 1980-85 the weight within the manufacturing sector of both defence contractors and the civilian companies increased. Defence firms gained considerably in terms of sales, employment, gross plants and company funded R&D in the latter period under the Reagan Administration. Whereas this may be considered a Reagan effect in defence procurement, other indicators point to in the opposite direction: (a) decrease in the shares of defence R&D contracts, (b) relatively low growth of patent output as percent of total manufacturing from the defence firms, and (c) decrease in scientific publications from defence firms per 1000 employees. Firm level analysis showed that military R&D contracts did not contribute to economic or technical efficiency. Space expenditure did not contribute to improvement of economic performance as measured by company growth and profitability. NASA contracts were not associated with technical progress measured by patents, but they improved scientific publications. Defence expenditures are not of importance for the overall economic efficiency. The standard financial variables, capital formation and own R&D activities prove mostly relevant. The study is restricted to an efficiency analysis in a cross sectional comparison and does not include the effect of market structure.
Keywords: 330